Electrochemical behavior of Mg electrode in sodium salt electrolyte system - Zhang, Yu; Zhu, Qingguang; Su, Chang; Li, Chao (Frontiers in Chemistry, 2022)
A suitable electrolyte is crucial to commercially available magnesium (Mg) batteries. Here, the influence of Na2SiO3 on the electrochemical behavior of AZ31 Mg alloy in the Na2SO4-NaNO3 composite electrolyte was investigated. The results revealed that the activation potential of AZ31B Mg alloy first represented a negative shift and then a positive shift with the increase of Na2SiO3. The most negative activation potential (−1.51 V) and the lowest polarization (−3.20 V) were found when 6 mM of Na2SiO3 was added; no discharge hysteresis was observed, and the polarization resistance value (R1) was 3806 Ω. After 24 h immersion in the composite electrolyte with Na2SiO3, more and wider cracks appeared on the alloy surface, where a thick, dense film was formed, showing excellent discharge performance and corrosion resistance.